BIOETANOL HASIL FERMENTASI KULIT PISANG KEPOK (Musa paradisiaca) DENGAN VARIASI RAGI MELALUI HIDROLISIS ASAM SULFAT - Hikmah Hikmah; Hilda Nur Fadhillah; Meilana Dharma Putra (EnviroScienteae, 2019)
Bioethanol is one of the biofuels that is present as an alternative fuel that is more environmentally friendly and renewable. This study aims to determine the effect of good temperatures in the process of hydrolysis for the manufacture of bioethanol, the effect of operating conditions for 5 days of good fermentation to produce large bioethanol and bioethanol levels produced by fermentation of banana kepok skin using yeast bread (Fermipan) and tape yeast, from both yeast to fermentation, which ones produce more bioethanol. This study of banana kepok peel dried into a powder. Banana skin powder was tested by FTIR, SEM, and XRD. The hydrolysis process with 0.5 N sulfuric acid in 500 mL with 25 grams of banana kepok peel powder. The hydrolysis process with temperature variations of 60ºC, 80ºC, and 100ºC. The hydrolysis solution is fermented with yeast variations, namely Fermipan and yeast tape (4 grams, 8 grams, and 12 grams) with the addition of NPK 4 grams and 5 gram urea. Results glucose levels were obtained at 60ºC, namely 33.0%, at 80ºC, 41.2% and temperatures of 100ºC, 56.0%. The results of fermentation solutions obtained by the concentration of ethanol in Fermipan with a weight of 4 grams, 8 grams and 12 grams respectively 0.264%, 0.630% and 0.786% while the concentration of ethanol in the tape yeast weighs 4 grams, 8 grams, and 12 grams successively which are 0.015%, 0.006% and 0.017%.